No sex differences in long-term functional outcome after intracerebral hemorrhage - De Ridder, Inger; Kuramatsu, Joji; Gerner, Stefan; Madzar, Dominik; Lücking, Hannes; Kloska, Stephan; Dippel, Diederik; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2017)
Background There is conflicting evidence about the influence of sex on outcome after spontaneous intracerebral hemorrhage (sICH) and the majority of the research focused on mortality and short-term outcome only. We investigated sex differences in long-term functional outcome after sICH. Methods We used data from a prospective hospital registry and included all consecutive patients with ICH admitted to our institution between January 2006 and July 2014. Functional outcome was assessed by modified Rankin Scale evaluated 3 and 12 months after ICH. We explored the influence of sex on long-term functional outcome using multivariable regression models and additionally by means of propensity score matching. Results We analyzed 823 patients, of whom 380 (46%) women. Women were on average three years older (p < 0.001), men had more often deep hematomas (p = 0.01). Unadjusted mortality rates were significantly increased in women at three months (42% vs. 35%; odds ratio (OR): 1.35; 95% confidence interval (CI): 1.02-1.80). After adjusting for baseline prognostic factors there were no differences between men and women in short- and long-term mortality (OR = 1.01; 95% CI = 0.66-1.54 and OR = 1.04; 95%CI = 0.69-1.57, respectively) and short- and long-term unfavorable outcome (OR = 1.02; 95%CI = 0.67-1.55 and OR = 0.96; 95% CI = 0.62-1.48, respectively). Conclusion We found no sex-related differences in long-term functional outcome in patients with sICH. The apparently worse functional outcome in women can be explained by differences in age.
EVALuna2:22516